Rb4Li2TiOGe4O12: A Titanyl Nonlinear Optical Material with the Widest Transparency Range. (22nd October 2019) - Xia, Mingjun; Tang, Chuan; Li, Rukang
Abstract: Practical mid‐infrared (MIR) coherent light beams generated by frequency conversion in nonlinear optical (NLO) crystals are indispensable in time‐resolved infrared vibrational spectroscopy, remote light detection and ranging, and free‐space communications. Herein, a new titanyl germanate Rb4 Li2 TiOGe4 O12 (RLTG) MIR NLO crystal was obtained by heavier element substitution. It features a complicated structure network composed of compressed TiO5 square pyramids and distorted GeO4 tetrahedra, separated by Rb + and Li + cations. More importantly, RLTG exhibits concurrently short ultraviolet (0.28 μm) and long IR (5.58 μm) transmittance cutoffs, fully covering the atmospheric transparent window of 3–5 μm. Related to the short UV cutoff, it shows a higher laser‐induced damage threshold in comparison to commercial MIR NLO crystals, about twice that of KTiOPO4 (KTP) and 50 times that of AgGaS2 (AGS). Abstract : Von kurz bis lang : Das kristalline Germanat Rb4 Li2 TiOGe4 O12, das nichtlineare optische Eigenschaften aufweist und als Quelle von mittlerem IR‐Licht wirkt, enthält gut ausgerichtete, komprimierte TiO5 ‐Gruppen sowie verzerrte GeO4 ‐Tetraeder und zeigt eine starke Frequenzverdopplung. Es zeichnet sich zugleich durch kurze UV‐ und lange IR‐Grenzwellenlängen aus und deckt so den Spektralbereich des atmosphärischen Fensters von 3 bis 5 μm vollständig ab.